Combining Ability and Heterosis for Grain Iron and Zinc Densities in Pearl Millet. Issue 2 (1st March 2013) - Govindaraj, M.; Rai, K. N.; Shanmugasundaram, P.; Dwivedi, S. L.; Sahrawat, K. L.; Muthaiah, A. R.; Rao, A. S.
ABSTRACT: Pearl millet [ Pennisetum glaucum (L.) R. Br.] is an important staple food crop in the semiarid tropical regions of Asia and Africa. As part of a major initiative to improve its grain Fe and Zn densities, two sets of line × tester studies were conducted. Results showed that the underlying physiological processes determining the grain Fe and Zn densities were largely under additive genetic control, and Fe and Zn densities of the inbred lines per se and their general combining ability (GCA) were positively and highly significantly correlated. This would imply that recurrent selection can be effectively used to improve the breeding populations for grain Fe and Zn densities and that breeding lines selected for high Fe and Zn densities per se are more likely to include those with high GCA for these micronutrients. Lack of better‐parent heterosis indicated that to breed hybrids with high Fe and Zn densities would require high levels of these micronutrients in both parental lines. Highly significant and positive correlations between the Fe and Zn densities, between the GCA of Fe and Zn densities, and between the specific combining ability (SCA) of the Fe and Zn densities showed that simultaneous selection for both micronutrients is likely to be effective with respect to all these performance parameters. Consistency in the patterns of results across both sets of trials and across the environments for all the parameters implies that these results could be of wider application to the genetic improvement of Fe and Zn densities in pearl millet.